Encyclopedia of Caribbean archaeology - Reid, Basil A., 1961-; Gilmore, R. Grant, III (Richard Grant) (University Press of Florida, 2014)
A sweeping overview of the scholarly information available on archaeology in the Caribbean, tackling the usual questions of colonization, adaptation, and evolution while embracing such newer aspects as geoinformatics and archaeometry.